2011
DOI: 10.1111/j.1751-1097.2011.01005.x
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Photosensitizers for Photodynamic Therapy of Infections Should Kill Bacteria but Spare Neutrophils

Abstract: Photodynamic therapy (PDT) for localized microbial infections exerts its therapeutic effect both by direct bacterial killing and also by the bactericidal effects of host neutrophils stimulated by PDT. Therefore, PDT-induced damage to neutrophils must be minimized, while direct photoinactivation of bacteria is maintained to maximize the therapeutic efficacy of antimicrobial PDT in vivo. However, there has been no study in which the cytocidal effect of PDT on neutrophils was investigated. In this study, the cyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(50 citation statements)
references
References 30 publications
1
46
0
2
Order By: Relevance
“…On the other hand, the hydrophilic TB exhibits limited diffusion into the double-layered phospholipid membrane of the mammalian cells, resulting in low cytocidal effects on host cells, as highlighted in several previous studies (62,63). This is an encouraging fact for the future clinical application of this photosensitizer (64).…”
Section: Discussionmentioning
confidence: 69%
“…On the other hand, the hydrophilic TB exhibits limited diffusion into the double-layered phospholipid membrane of the mammalian cells, resulting in low cytocidal effects on host cells, as highlighted in several previous studies (62,63). This is an encouraging fact for the future clinical application of this photosensitizer (64).…”
Section: Discussionmentioning
confidence: 69%
“…Although few studies have focused on the potential effects of PDT with phenothiazinium dyes on healthy cells or the immune system, some studies have investigated the action of PDT on fibroblasts, keratinocytes, or neutrophils [45][46][47]. Tanaka et al [47] In conventional treatment of bovine mastitis, topical antibiotic is applied through the teat canal of the mammary gland after milking. For this reason, we believe that for PDT clinical trials, PS should be administered after milking, as well as a conventional treatment.…”
Section: Regardlessmentioning
confidence: 99%
“…However, factors such as the pharmacokinetics of the PS, the use of an adequate wavelength and both irradiation and incubation protocols may affect the outcome of the procedure. The protocol used in the present study is clinically promising and this is probably one of the first reports on the effective use of direct topical application of PACT using TBO in infected bone.A study of cytotoxicity of PACT on neutrophils [27] concluded that the use of this therapy may preserve the viability of the cells helping in the control of the infection. An important finding from the present study is that, the group treated with PACT presented predominantly absence of acute inflammation, typical phase in which neutrophils are present.…”
Section: Discussionmentioning
confidence: 97%